Ordered structures of alkylated carbon dots and their applications in nonlinear optics. Issue 26 (12th June 2020) - Yin, Keyang; Lu, Dandan; Tian, Wendong; Zhang, Rui; Yu, Haohai; Gorecka, Ewa; Pociecha, Damian; Godbert, Nicolas; Hao, Junying; Li, Hongguang
Abstract : C dots with peripheral alkyl chains have been prepared, which undergo self-organization in the solvent-free state. A nonlinear optical response with reverse saturable absorption behavior has been found in the film state, which opens the door for potential applications in laser protection. Abstract : Manipulation of the long-range organization of nanomaterials plays a key role in expanding their applications. Specifically for carbon nanomaterials, the ordering of fullerenes, which have a defined molecular structure, has been extensively studied. However, for the members which are polydisperse in size and shape, such as carbon nanotubes, graphene and the newly discovered carbon dots (C dots), the control of their supramolecular organization becomes highly challenging. In this work, we prepared alkylated C dots by mild pyrolysis of aliphatic amines in chlorobenzene, which can be further sorted based on their polarity through silica gel chromatography. These C dots have tiny, planar cores surrounded by peripheral alkyl chains, and can self-organize into highly ordered crystals or soft crystals with lamellar arrangements in a solvent-free state. As a typical example of applications, the nonlinear optical response of the C dots was investigated in the film state without any other additive. Reverse saturable absorption behavior has been found, and the nonlinear absorption coefficient is closely related to the content of the carbon nitride inside the C dots, revealing that their nonlinear optical response is governed by the higher absorption cross section of the excited-state induced by the π-conjugated structure. These new C dots could find applications in laser protection as they can be used for making flexible and even wearable thin films. In addition, other potential applications could also be envisaged, such as being new candidates for the production of high-quality carbon fibers.